Publication of the results of the International Musa Testing Programme, Phase III (IMTP III) - Crichton, R.; Bergh, Inge van den (International Society for Horticultural Science, 2016)
The International Musa Testing Programme (IMTP) was set up to evaluate the performance of banana synthetic hybrids and somaclonal variants, as well as traditional cultivars and wild Musa species, in the presence of biotic and abiotic constraints in multi-locational field trials around the world. Three phases of the IMTP have been conducted. The report on the results of the most recent phase, IMTP III, is expected to be published in early 2016. The upcoming publication reports on the results of 16 field trials conducted by 14 partners in 12 countries; evaluating 23 synthetic hybrids, 2 somaclonal variants, 36 cultivars and 3 wild Musa species; in the presence of the biotic constraints of Mycosphaerella fijiensis, Mycosphaerella musicola, Fusarium oxysporum f. sp. cubense, and various nematode species. The IMTP III report includes results for the following variables: time from planting to shooting, time from planting to harvest, plant height, plant girth, height of the following sucker, number of functional leaves at shooting, number of functional leaves at harvest, leaf emission rate, bunch weight, annual yield, number of hands, number of fruits, number of fruits in hand, fruit weight, fruit length, youngest leaf spotted at shooting, youngest leaf spotted at harvest, and disease development time. The results of the average annual yield across all trials are reported in this paper, with 'FHIA-25' having the greatest yield of 51.8 t ha-1 y-1. To address issues in the experimental design of IMTP III that made direct comparison between the different genotypes and field trials difficult, and that did not take traits that are important to consumers into account, the IMTP has been redesigned and new guidelines for conducting banana germplasm evaluations are expected to be released in 2016.